ANALISIS PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP NET PROFIT MARGIN PADA PERUSAHAAN INDUSTRI PLASTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - B11108010, DELLA DEVIANA PUTRI (Jurnal Manajemen Update, 2012)
ABSTRACT The research aimed to know the effect of liquidity and leverage to Net Profit Margin. The object of the research is ten industry plastics companies for the years 2006 until 2010. The research method is kausal method and descriptive method. The method of analysis used is multiple linear regression analysis. The results showed that the variables in this study have normal distribution. And at the multicollinearity test results also stated that there is no multicollinearity problem among the independent variables. The results of analysis by F test hypotheses simultaneously conclude that CR, QR, DAR and DER significantly influence NPM t test as for the CR, QR and DER has concluded that the variable effect on NPM, whereas DAR variable has no effect on NPM. Keywords : liquidity, leverage, profitability